Biodiversity of Freshwater Fish in Kelekar Floodplain Ogan Ilir Regency in Indonesia - Muslim Muslim; Mochamad Syaifudin (Journal of Tropical Biodiversity and Biotechnology, 2022)
The purpose of this study is to investigate fish biodiversity in the Kelekar floodplain. The study is explorative, with the determination of observation stations and with purposive sampling methods. Fishes were captured approximately 1.509 individuals consisting of 17 families and 24 species. The Shannon-Weiner diversity index was 2.394; 2.691; and 2.183 for station 1, 2, and 3, respectively. The Evenness index was 0.764; 0.871; and 0.806 for station 1, 2, and 3, respectively, meanwhile the highest value of Simpson’s dominance index was 0.045. The biodiversity index of the three stations was in the medium category.